Porcentajes de harina de bledo (Amaranthus Dubius) en las características fisicoquímicas, nutricionales y sensoriales de un yogur batido - Intriago Daza, Lauro Andrés (2023)
The objective of this research was to determine a suitable percentage that meets the physicochemical, nutritional, toxicological and sensory characteristics of a whipped yogurt, in order to determine an adequate percentage that meets the characteristics Physicochemical, nutritional, toxicological and sensory characteristics of a yogurt. For its effect, 4 treatments were carried out with different percentages of flour (0.50, 1, 1.5, and 2), the same ones that were later analyzed for pH, ° Brix, acidity, syneresis, viscosity, total solids, proteins, fiber, coliforms totals, Escherichia coli, molds and yeasts, allergenic toxicity, bioeasy aflatoxin m1, and sensory characteristics. The results showed that the pigeon flour presented a non-allergenic behavior for 5 samples out of 6 that were analyzed. In addition, it will be verified that, with a higher percentage of established flour, the values of °Brix, protein and syneresis will increase, however, they are all within the limits. The treatments in the microbiological field did not present the presence of Escherichia coli, however, certain traits of total coliforms were found, of which said values are within the established limits. The treatments that presented the best physical-chemical and nutritional characteristics underwent an aflatoxin analysis using a quantitative method and the result was favorable since none exceeded the limits established by the regulations. Treatment 1 was the most accepted according to the sensory analysis performed.